Impact of Feedback in Flipped Learning on the Development of Soft Skills of University Students - Ricardo Sanchez-Gil-Machín; Salvador Baena Morales; Nuria Molina-García; Alberto Ferriz-Valero (Education Sciences)
This study investigates the impact of flipped learning (FL) with and without teacher feedback on resilience and perceived professional competence among university students. This quasi-experimental study, conducted over three academic years, involved 255 s-year students (mean age = 20.47 ± 2.63; 60.4% female) enrolled in a Primary Education Teaching degree program at a Spanish public university. Participants were divided into two treatment groups: Feedback FL and Non-feedback FL. Validated scales—the Brief Resilience Scale (BRS) and the Perceived Competence Scale for Students (PCNS)—were used for pre- and post-intervention assessments. Both groups demonstrated significant improvements in resilience and perceived competence, with no statistically significant differences between the Feedback FL and Non-feedback FL groups. Data analysis included Mann–Whitney U tests for inter-group comparisons, Wilcoxon tests for intra-group comparisons, and 2 × 2 repeated measures ANOVA, which revealed no interaction effects (Time × Treatment) for either variable. These results suggest that FL alone fosters the development of transversal skills such as resilience and perceived competence, regardless of teacher feedback. The findings highlight the effectiveness of active learning models like FL in higher education for promoting essential competencies. Future research should address additional soft skills and employ larger, more diverse samples to further explore the role of feedback and innovative methodologies in enhancing FL’s impact.